A dog's way home [large type] - Cameron, W. Bruce (Wheeler Publishing, 2017)
From the author of the #1 New York Times bestseller and film A Dog's Purpose comes a classic story of unwavering loyalty and incredible devotion. A Dog's Way Home is the story of Bella, a pit bull puppy rescued by Lucas Ray, and her seemingly impossible and completely unforgettable journey home to him.